Emulating a target trial of proton pump inhibitors and dementia risk using claims data. (25th February 2022) - Ahn, Nayeon; Nolde, Michael; Günter, Alexander; Güntner, Florian; Gerlach, Roman; Tauscher, Martin; Amann, Ute; Linseisen, Jakob; Meisinger, Christa; Rückert‐Eheberg, Ina‐Maria; Baumeister, Sebastian‐Edgar
Abstract: Background and purpose: Understanding the adverse effects of proton pump inhibitors (PPIs) is important due to their widespread use, but the available evidence for an increased dementia risk amongst patients taking PPIs is inconclusive. The present study aimed to estimate the causal effect of PPIs on the risk of dementia by target trial emulation and time‐varying exposure modeling. Methods: Using claims data of 2, 698, 176 insured people of a large German statutory health insurer, a target trial was conceptualized in which individuals aged 40 years and older were classified as PPI initiators or non‐initiators between 2008 and 2018, and were followed until diagnosis of dementia, death, loss to follow‐up or end of study. Incidence of dementia (International Classification of Diseases 10 codes F00, F01, F03, F05.1, G30, G31.0, G31.1, G31.9 and F02.8+G31.82) was defined applying a 1‐year lag window. Weighted Cox models were used to estimate the effect of PPI initiation versus non‐initiation on dementia risk and weighted pooled logistic regression was used to estimate the effect of time‐varying use versus non‐use. Results: In all, 29, 746 PPI initiators (4.4%) and 26, 830 non‐initiators (1.3%) were diagnosed with dementia. Comparing PPI initiation with no initiation, the hazard ratio for dementia was 1.54 (95% confidence interval 1.51–1.58). The hazard ratio for time‐dependent PPI use versus non‐use was 1.56 (95% confidence interval 1.50–1.63). Differentiated subtypes, including unspecified dementia, Alzheimer's disease and vascular dementia, showed increased risk by PPI initiation and time‐varying PPI use. Conclusions: This study suggests that PPI initiation and time‐varying PPI use may increase overall dementia risk. Abstract : The causal effect of proton pump inhibitors (PPIs) on the risk of dementia was estimated by a target trial emulation and time‐varying exposure modeling using claims data of 2, 698, 176 insured people of a large German statutory health insurer between 2008 and 2018. Our findings suggest that PPI initiation and its long‐term use may increase overall dementia risk.